1986
DOI: 10.1073/pnas.83.15.5410
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of vesicular stomatitis virus in vitro RNA synthesis by microtubule-associated proteins.

Abstract: Microtubule-associated proteins purified from bovine brains stimulated the in vitro transcription and replication reactions of vesicular stomatitis virus. The products of these reactions were intact messenger or genome-sized RNA species. A preparation from HeLa cells containing tubulin and microtubule-associated proteins also stimulated vesicular stomatitis virus transcription in vitro. This observation is in accord with previous studies, which suggested that a host cell factor was involved with the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Previously we had reported that tubulin had very little stimulatory effect on an in vitro transcription reaction containing purified VSV RNPs whereas purified MAPs stimulated the reaction by up to 16-fold (Hill et al, 1986). As seen in Table 1, addition of purified tubulin to the reconstituted system resulted in no stimulation of incorporation.…”
Section: The Effect Of M a P S And Tubulin On A Reconstituted In Vitrmentioning
confidence: 79%
See 4 more Smart Citations
“…Previously we had reported that tubulin had very little stimulatory effect on an in vitro transcription reaction containing purified VSV RNPs whereas purified MAPs stimulated the reaction by up to 16-fold (Hill et al, 1986). As seen in Table 1, addition of purified tubulin to the reconstituted system resulted in no stimulation of incorporation.…”
Section: The Effect Of M a P S And Tubulin On A Reconstituted In Vitrmentioning
confidence: 79%
“…Moyer et al (1986), reported that tubulin stimulated VSV transcription in vitro by two-to seven-fold and that tubulin was an absolute requirement for Sendai virus transcription in vitro. Our previous data indicated that partially purified MAPs, and not tubulin, stimulated VSV transcription in vitro (Hill et al, 1986). Furthermore, we have observed recently that Sendai virus transcription in vitro, using the system of Dethlefsen & Kolakofsky (1983), was stimulated fivefold by bovine brain MAPs resulting in full-length transcripts (data not shown).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations